Impacto da atenção farmacêutica - Neto, Paulo Roque Obreli; Vieira, Jessika Caroline; Cuman, Roberto Kenji Nakamura (Experiências Exitosas de Farmacêuticos no SUS, 2015)
Impacto da atenção farmacêutica